Artistic research and practice-based methodologies in music performance studies: a personal reflection - Telles, Ana (2022)
The study of musical phenomenon has, for a long time, unfolded in two separate camps: indeed, declarative knowledge was mainly produced in universities, where Musicology and its different disciplines were taught, whereas procedural knowledge associated with the performance and composition of Music stemmed mostly from conservatories, music academies and active musicians. Quite recently, the central role of performance in the musicological debate, away from the supremacy of the written text (score), has been pointed out. Indeed, through his seminal writings on music as performance, Nicholas Cook (2014) suggested the centrality of performance in the investigation of the musical phenomenon. In the meanwhile, several authors and institutions have contributed to the definition of “artistic research” in Music (cf. AEC, 2015); it is understood that this specific type of research effectively combines declarative and procedural knowledge through practice-based objects, methods, and outcomes. As regards the enquiry about musical practice and creation, Pinheiro and Caires (2019) identified four levels of reflective depth to which I will relate, in the lines below, my most significant research projects. In doing so, I am drawn to conclude that my practice-based objetcts and methods have enabled me to achieve results otherwise not possible to tackle, while acknowledging that complementary methods (including from Social Sciences and Humanities) are necessary and beneficial. Even if artistic research in different artistic disciplines supposes an array of specific and differentiated methodological approaches, it benefits from interdisciplinary cooperation, as it shares identical purposes, large-scale methodologies and overarching preoccupations.